(untitled) (International Journal of Food and Nutritional Sciences, 2024)
This qualitative study explores the impact of a school-based Nutrition Awareness Programme on the lifestyle choices of secondary school students. Adolescence represents a formative stage in which individuals establish habits that influence lifelong health and well-being. Recognizing the importance of early nutrition education, this study examined how adolescents internalize and apply nutritional knowledge in their everyday lives. Using a thematic analysis approach, data were collected from open-ended questionnaires administered to students who participated in a structured nutrition awareness intervention Programme. The analysis yielded five overarching themes: (1) Knowledge Acquisition, (2) Knowledge Application, (3) Behavioral Changes, (4) Programme Evaluation, and (5) Action Planning and Lifestyle Modification. Students reported enhanced understanding of dietary balance, nutrition labelling, and mindful eating, which translated into meaningful lifestyle shifts such as increased consumption of fruits and vegetables, reduced intake of processed foods, and greater awareness of healthy living. The findings highlight the potential of experiential, school-based nutrition education to promote sustainable lifestyle changes and holistic well-being among adolescents. The study advocates integrating nutrition awareness modules into secondary education curricula to cultivate lifelong healthy habits, aligning with the goals of holistic learner development envisioned in the National Education Policy (NEP) 2020.